Linking climate change to land surface change - McLaren, Sue J.; Kniveton, Dominic R. (Dordrecht : Springer Netherlands, 2000)
Our views and understanding of variations in climate, geomorphological processes and the interrelationships that exist between climatic changes and land surface changes, both now and in the past, have developed greatly over the last decade. This book aims to encapsulate some of these recent advances and focuses on the integration of research that has been conducted by geomorphologists and climatologists on linking climate and land surface changes. This book is divided into two main parts: Section A incorporates research that has concentrated on short-term variations in climate, whilst Section B looks at some of the work on long-term climate variability. The volume concludes with a summary chapter that brings together the various ideas that have been presented in this work and other recent research in this general field. This text will be of interest to upper level students of geomorphology, Quaternary studies, climatology, earth sciences, and environmental studies. It will also be of use to researchers in these fields.
Short-Term Climate Variabilyty -- Dust Variability over Northern Africa and Rainfall in the Sahel -- Desiccation in the Sahel -- Hydrological Response of Desert Margins to Climatic Change: The Effect of Changing Surface Properties -- Weathering, Geomorphology and Climatic Variability in the Central Namib Desert -- Warm Season Land Surface - Climate Interactions in the United States Midwest from Mesoscale Observations -- Streamflow Changes in the Sierra Nevada, California, Simulated Using a Statistically Downscaled General Circulation Model Scenario of Climate Change -- Examining Links between Climate Change and Landslide Activity Using GCMS -- Long-Term Climate Variability -- Geologic Evidence of Rapid, Multiple, and High-Magnitude Climate Change During the Last Glacial (Wisconsinan) of North America -- Aeolian Geomorphic Response to Climate Change: An Example from the Estancia Valley, Central New Mexico, USA -- Evaporite Minerals and Organic Horizons in Sedimentary Sequences in the Libyan Fezzan: Implications for Palaeoenvironmental Reconstruction -- Relict Cryogenic Mounds in the UK as Evidence of Climate Change -- Investigations into Long-Term Future Climate Changes -- Summary -- Geomorphological and Climatological Perspectives on Land Surface -Climate Change.
Elektronická reprodukce.
Keywords: klimatické změny; geomorfologie; hydrogeomorfologie; climate changes; geomorphology; hydrogeomorfology; e-knihy online; e-books online